Biophysical-based sustainable management of KHDTK Mungku Baru: Mapping conservation, research and utilization blocks - Hanaf, Nanang; Jauhari, Ahmad; Hatta, Gusti Muhammad; Hafizianor (Agriculture and Natural Resources, 2025)
Importance of the work: Sustainable management of Special Purpose Forest Area (KHDTK) Mungku Baru, requires area planning based on mapping and determining management blocks that are in accordance with biophysical conditions. Objectives: To create management plots based on watershed boundaries and group them into management blocks based on biophysical conditions: vegetation density, land surface temperature, carbon stock and land cover type. Materials and Methods: Management plots were designed by considering watershed boundaries using the Digital elevation model (DEM), normalized vegetation index (NDVI) analysis and land surface temperature (LST) analysis based on Landsat 9 imagery, carbon stock analysis and land cover analysis. Management blocks were created based on a weighted overlay of management plots with NDVI, LST, carbon stock and land cover. Results: The overlay of management plots, NDVI, LST, land cover and carbon stocks produced 26 conservation blocks, with an additional 24 plots in the research and development block, 6 plots in the indigenous cultural block and utilization and 6 plots in the rehabilitation block. The minimum area limit for KHDTK utilization was no more than 10% of the area, in accordance with applicable regulations. Main finding: The arrangement of the KHDTK Mungku Baru area was designed by creating management blocks according to biophysical conditions, with the aim being to ensure the sustainability of the KHDTK Mungku Baru.